(untitled) (Global Journal of Science Frontier Research, 2015)
This paper presents the results of physico-chemical parameter data and water quality index used to assess the groundwater quality around Olusosun and Solus dumpsites in Lagos southwest, Nigeria. Twenty (20) water samples each were collected in wells and boreholes around these two dumpsites, once in two months consecutively for two years. The parameters determined include pH, acidity, alkalinity, conductivity (EC), total dissolved solids (TDS), total hardness (TH), Cl-, SO42-, NO3-and PO43-and heavy metals: Pb, Ni, Cd, Zn, Cu, Fe, Mg, Ca, Na and K using standard analytical methods. Descriptive statistics and correlation coefficient were carried out on the data generated. There is strong correlation at p < 0.05 in some of the parameters such as TDS versus EC (r = 0.95), TDS versus TS (r = 0.90), TH versus acidity (r = 0.73) in Olusosun while TDS versus EC (r = 0.93), TDS versus acidity (r = 0.82), TH versus alkalinity (r = 0.77) in Solus, suggesting common source. However, very weak chemical associations (r < 0.30) were observed in majority of the quality parameters particularly anions and trace metals, indicating multiple anthropogenic sources.